Selective Laser Trabeculoplasty Outcomes in Phakic and Pseudophakic Patients: A Meta-Analysis - Rushil Kumbhani; Amanda Wong; Aretha Zhu; Paras Shah; Tristan Tham; Farihah Anwar; Daniel Zhu (Journal of Current Ophthalmology)
Purpose: To perform a meta-analysis to compare the efficacy of selective laser trabeculoplasty (SLT) in phakic and pseudophakic eyes. Methods: Scopus, Embase, PubMed, and gray literature were searched for studies comparing SLT outcomes in phakic and pseudophakic patients with open-angle glaucoma (OAG) or ocular hypertension (OHT). The mean change in intraocular pressure was compared using a standardized mean difference (SMD) meta-analysis (RevMan 5.4.1). Begg’s funnel plots and Egger’s test were used to assess publication bias. Results: Eleven studies with 1058 eyes (323 pseudophakic and 735 phakic) were identified. There was no statistically significant difference in the observed efficacy of SLT between pseudophakic and phakic eyes (SMD = −0.10; 95% confidence interval = −0.24, 0.03; P = 0.14). There was no publication bias or heterogeneity (I2 = 0%; P = 0.66) detected. Subgroup analysis of studies stratified by length of follow-up in months (6, 12, and 24 or greater) revealed no significant difference in SLT efficacy at the different time points (P = 0.86, P = 0.59, and P = 0.16, respectively). Conclusions: Our pooled and subgroup analysis revealed no significant difference in SLT response between the two populations. Our results support SLT as a viable treatment option for patients with OAG or OHT regardless of pseudophakic status.